WDR19: An ancient, retrograde, intraflagellar ciliary protein is mutated in autosomal recessive retinitis pigmentosa and in Senior‐Loken syndrome. (9th July 2013) - Coussa, R G; Otto, E A; Gee, H‐Y; Arthurs, P; Ren, H; Lopez, I; Keser, V; Fu, Q; Faingold, R; Khan, A; Schwartzentruber, J; Majewski, J; et al.
Abstract : Autosomal recessive retinitis pigmentosa (arRP) is a clinically and genetically heterogeneous retinal disease that causes blindness. Our purpose was to identify the causal gene, describe the phenotype and delineate the mutation spectrum in a consanguineous Quebec arRP family. We performed Arrayed Primer Extension (APEX) technology to exclude ∼500 arRP mutations in ∼20 genes. Homozygosity mapping [single nucleotide polymorphism (SNP) genotyping] identified 10 novel significant homozygous regions. We performed next generation sequencing and whole exome capture. Sanger sequencing provided cosegregation. We screened another 150 retinitis pigmentosa (RP) and 200 patients with Senior‐Løken Syndrome (SLS). We identified a novel missense mutation in WDR19, c.2129T>C which lead to a p.Leu710Ser. We found the same mutation in a second Quebec arRP family. Interestingly, two of seven affected members of the original family developed 'sub‐clinical' renal cysts. We hypothesized that more severe WDR19 mutations may lead to severe ciliopathies and found seven WDR19 mutations in five SLS families. We identified a new gene for both arRP and SLS. WDR19 is a ciliary protein associated with the intraflagellar transport machinery. We are currently investigating the full extent of the mutation spectrum. Our findings are crucial in expanding the understanding of childhood blindness and identifying new genes.